(untitled) (Bangladesh Journal of Otorhinolaryngology, 2009)
Incidence of benign thyroid adenoma is common, but adenoma causing extensive skin ulceration is a very unusual presentation. Here we are reporting a case of a 70-year-old female from Norshingdi district who presented to us with an ulcerated, neck swelling over the thyroid region for one year, which moves with deglutition and bleeds on touch with foul smelling discharge for one month and pain for two months. Biopsy from the ulcer revealed inflammatory lesion while subsequent histopathology following thyroidectomy under local anesthesia gave features of follicular adenoma. Postoperative period was satisfactory and follow up was excellent. Key words: Follicular adenoma, Thyroid, Skin ulcer. DOI: 10.3329/bjo.v14i1.3278 Bangladesh J of Otorhinolaryngology 2008; 14(1) : 36-38